"Are you calling me a liar"? Clinical interviewing more for trust than knowledge with high-risk men with antisocial personality disorder. Issue 4 (2nd October 2018) - Ramsden, Jo
Abstract: Clinical interviewing with a population who tend to mistrust interpersonal communication is complex and challenging. This paper argues that, traditionally, the basis on which these types of interviews are conducted (to gather information to inform a diagnosis or formulation) has the potential to compound the difficulties. An approach is outlined which challenges implicit assumptions about the neutrality of the interview and assumes, instead, that 'personality disorder' emerges from the failures in communication which often characterise these encounters. Workers are invited to understand how they themselves, their assumptions and routine organisational practices contribute to this dynamic process. They are invited to work instead with a focus on building trust and learning collaboratively about what helps. Understanding risk issues is considered to be an intrinsic part of this process given that the emotional events which underpin risk are assumed to be inevitably 'live' within the interview.